2020
DOI: 10.1007/s43452-020-00035-z
|View full text |Cite
|
Sign up to set email alerts
|

Research of mechanical and electrical properties of Cu–Sc and Cu–Zr alloys

Abstract: The research paper presents the impact of the scandium additive and various conditions of the heat treatment on copper mechanical, electrical and heat resistance properties. The performed research works included manufacturing of CuSc0.15 and CuSc0.3 alloys through metallurgical synthesis with the use of induction furnace and following crystallization in graphite crucibles at ambient temperature. Additionally, a CuZr0.15 alloy was produced as a reference material for previously synthesized Cu-Sc alloys. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…All experimental data on the hardness and electrical conductivity of specimens, without cold working performed prior to aging, were consistent and correlated with the published results of Franczak et al [33]. Furthermore, the investigated visual precipitates appeared in lamellar structures, corresponding to the published investigation of strengthening effects [35] and their expected structure [2].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…All experimental data on the hardness and electrical conductivity of specimens, without cold working performed prior to aging, were consistent and correlated with the published results of Franczak et al [33]. Furthermore, the investigated visual precipitates appeared in lamellar structures, corresponding to the published investigation of strengthening effects [35] and their expected structure [2].…”
Section: Discussionsupporting
confidence: 90%
“…Hao et al demonstrated the precipitation mechanisms, formation, and growth of Cu 4 Sc phases from the supersaturated solid solution, with detailed TEM investigations [35]. Focusing on moderate degrees of cold deformation before the aging process, the conducted research closed the gap between specimens aged directly after solution annealing and quenching, by Franczac et al [33], and specimens with enhanced degrees of deformation prior to the aging process, by Hao et al [35]. Referring to Hao et al, XRD measurements were conducted to verify the same crystallographic structure of the precipitates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently published studies by Franczak et al [8] and Dölling et al [9] show that a combination of copper and scandium elements has potential in terms of electrical conductivity and mechanical strength in addition to having advantages in terms of recrystallization behavior and grain refinement [9][10][11]. In particular, cold working prior to precipitation hardening increases the density of dislocations and strain-induced defects in the material, creating more nucleation sites for the precipitation of the fine precipitates.…”
Section: Introductionmentioning
confidence: 99%